2019
DOI: 10.1111/and.13419
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of treatment methods for recurrent varicoceles to compare post‐treatment sperm parameters, pregnancy and complication rates

Abstract: We aimed to define which method would be the best for the treatment of recurrent varicoceles. We analysed 21 studies to compare post‐treatment improvement in semen parameters, spontaneous pregnancy and complication rates between the treatment methods. Overall spontaneous pregnancy rate was significantly higher in the surgical methods (44.3%) than in the radiological interventions (17.9%; p = .007). Post‐treatment improvement rates in sperm parameters were significantly higher in the open surgical methods (77.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…The surgical procedure presented a relapse rate of 12.4% (15 cases on 121) in our casuistry, independently of the technique applied. This rate is in line with data available in the literature 46 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The surgical procedure presented a relapse rate of 12.4% (15 cases on 121) in our casuistry, independently of the technique applied. This rate is in line with data available in the literature 46 …”
Section: Discussionsupporting
confidence: 92%
“…This rate is in line with data available in the literature. 46 Our study has several limits, such as the retrospective study design and the imbalance among surgical approaches. Indeed, the study does not provide a case-control approach to compare the surgical techniques.…”
Section: Detection Of Covid-19 In the Male Reproductive Tractmentioning
confidence: 99%
“…If treatment of varicocele is preferred, improvement of testosterone level will take some time, and if ART is preferred to conceive, testosterone treatment might be given to these hypogonadal men for hypogonadism related symptoms [8,9]. Varicocele in hypogonadal men can be treated via open surgery, radiologic interventions and laparoscopic approaches [24,25]. When all the methods in the literature are compared, microsurgical varicocelectomy provides the lowest complications rates, including varicocele recurrence, testicular atrophy and hydrocele formation, compared to other varicocelectomy methods.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that the rate of wound infection and hematoma post varicocelectomy has the lowest rate of 1.1% with microsurgical approach. 4 However, a one center study was conducted to examine the return to the hospital after ambulatory surgery discharge showed that patients underwent varicocelectomy and hydrocelectomy are 8.3 times more likely to return to the hospital than other ambulatory surgeries, two-thirds of them were evaluated for infections and fever. 5 …”
Section: Discussionmentioning
confidence: 99%